2024
DOI: 10.1101/2024.02.14.580389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translational response to mitochondrial stresses is orchestrated by tRNA modifications

Sherif Rashad,
Shadi Al-Mesitef,
Abdulrahman Mousa
et al.

Abstract: Mitochondrial stress and dysfunction play important roles in many pathologies. However, how cells respond to mitochondrial stress is not fully understood. Here, we examined the translational response to electron transport chain (ETC) inhibition and arsenite induced mitochondrial stresses. Our analysis revealed that during mitochondrial stress, tRNA modifications (namely f5C, hm5C, queuosine and its derivatives, and mcm5U) dynamically change to fine tune codon decoding, usage, and optimality. These changes in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…In our work, we identified queuosine (tRNA-Q) to be preferentially enriched in the brain and drive NAY codon recognition. Queuosine modifications were shown to play important role in regulating cellular response to arsenite induced oxidative stress and mitochondrial stress and dysfunction (15,23), as well as playing a role in hippocampal neurons function and cognition (17). Interestingly, despite the reported importance of queuosine in codon decoding in vitro (18,23), Knockout mice were phenotypically normal apart from cognitive and memory dysfunction (17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our work, we identified queuosine (tRNA-Q) to be preferentially enriched in the brain and drive NAY codon recognition. Queuosine modifications were shown to play important role in regulating cellular response to arsenite induced oxidative stress and mitochondrial stress and dysfunction (15,23), as well as playing a role in hippocampal neurons function and cognition (17). Interestingly, despite the reported importance of queuosine in codon decoding in vitro (18,23), Knockout mice were phenotypically normal apart from cognitive and memory dysfunction (17).…”
Section: Discussionmentioning
confidence: 99%
“…Queuosine modifications were shown to play important role in regulating cellular response to arsenite induced oxidative stress and mitochondrial stress and dysfunction (15,23), as well as playing a role in hippocampal neurons function and cognition (17). Interestingly, despite the reported importance of queuosine in codon decoding in vitro (18,23), Knockout mice were phenotypically normal apart from cognitive and memory dysfunction (17). In addition, such distinct phenotype indicates the importance of tRNA-Q in brain function, in line with previous works that showed that Queuine, the precursor for queuosine, is protective against neurodegenerative diseases (38) and our observation of queuosine enrichment in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reinforced the importance of Q as a micronutrient [ 10 , 11 ], particularly for optimal brain function [ 12 , 13 ] and mitochondrial stress responses [ 14 ]. However, how the human host competes with organisms of the microbiome for Q precursors is poorly understood.…”
Section: Introductionmentioning
confidence: 99%